Narrative Community in Edna Alford’s A Sleep Full of Dreams - Lalonde, Jeremy (Studies in Canadian Literature / Études en littérature canadienne, 2004)
A Sleep Full of Dreams must be read as an experimental text: Edna Alford courts disunity within the sequence of stories, limiting the centripetal power that a unified setting or a sustained development of Arla's character would lend. Instead, Alford employs imagistic and linguistic links as textual redirections which, complemented by shifts between narrative points of view, compel the reader to view the Pine Mountain Lodge community in its totality. While Arla prefers to either idealize or ignore the women of the Lodge, Alford carefully demonstrates the dangers of both responses, allowing her characters to emerge as imperfect and fully formed individuals.